DEVELOPMENT OF SCIENCE GAMES MEDIA ON THE INTERACTION BETWEEN THE COMPONENTS OF AN ECOSYSTEM - Zahrah, Ainiah; Nestiadi, Adi; Kurniasih, Septi (Universitas Bhinneka PGRI, 2026)
This study aims to create an interactive learning tool in the form of an Android-based science game to teach seventh-grade junior high school students about the interactions among ecosystem components. The issue addressed is the students' low understanding of concepts due to a lack of engaging and interactive learning materials. The methodology employed is research and development (RandD) using a modified version of the ADDIE model (analysis, design, development, implementation, and evaluation). The product is developed with the Unity platform, incorporating avatars, images, sounds, and videos to enhance its appeal and cater to students' learning preferences. A discovery learning approach is utilized to encourage students to explore and grasp concepts independently. Validation by media experts, subject matter specialists, and educational practitioners yielded highly valid results, while trials conducted with junior high school students showed excellent feedback and improvements in learning outcomes exceeding the Minimum Completeness Criteria (KKM). The findings indicate that the Android-based science game is effective and suitable as a learning medium to enhance understanding of ecosystem concepts.